2017
DOI: 10.1108/jcre-03-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Occupier responses to sustainable real estate: what’s next?

Abstract: Purpose-The purpose of this paper is twofold. Primarily, it examines the relationship between sustainable buildings and occupiers, by summarising the key extant literature. Secondarily, the paper proposes avenues for future research relating to the impact of sustainability on corporate real estate strategy. Design/methodology/approach-The paper reviews over ninety relevant publications related to sustainability, real estate market responses and corporate real estate, focussing on the role and response of occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Among the private topics of sustainability, we observe the concern of real estate entities about the environmental issues, especially climate change, carbon emissions and energy consumption, which are actually the issues that most concern the academic, political and professional representatives [60,66]. Even though the literature "makes reference to the holistic nature of the sustainability concept" ( [60], (p. 746)), there is "a market tendency to consider buildings with high ratings for environmental performance as sustainable" ( [67], (p. 6)). Because the market recognises sustainability as a competitive factor that adds value to a property, real estate companies create new strategies and investment fields based on sustainable principles in order to ensure positive financial outcomes (lower operating costs, higher lease rates, higher occupancy rates and lower tenant fluctuation).…”
Section: Summary and Concluding Discussionmentioning
confidence: 99%
“…Among the private topics of sustainability, we observe the concern of real estate entities about the environmental issues, especially climate change, carbon emissions and energy consumption, which are actually the issues that most concern the academic, political and professional representatives [60,66]. Even though the literature "makes reference to the holistic nature of the sustainability concept" ( [60], (p. 746)), there is "a market tendency to consider buildings with high ratings for environmental performance as sustainable" ( [67], (p. 6)). Because the market recognises sustainability as a competitive factor that adds value to a property, real estate companies create new strategies and investment fields based on sustainable principles in order to ensure positive financial outcomes (lower operating costs, higher lease rates, higher occupancy rates and lower tenant fluctuation).…”
Section: Summary and Concluding Discussionmentioning
confidence: 99%
“…The possibility to achieve higher rents encourages investors to develop green buildings, even if there might be a cost premium associated with the development of those buildings (e.g., [55]). Tenants' willingness to pay higher rents in certified buildings is associated with improved productivity and other corporate-level benefits, as well as lower operating costs, if they are responsible for the operating expenses of leased premises [55,72,73]. The consideration of lease structures and inclusion of operating expenses affect the results of rent premium analysis, which is discussed in more detail later in this section and in Section 4.2.…”
Section: Rental Premiumsmentioning
confidence: 99%
“…A review of the occupiers' perspective on green buildings from the 'business case' has been outlined by Livingstone and Ferm [4] which highlighted occupiers' motivations fall primarily into three areas: (i) reduced operational costs (property level driver); (ii) enhanced productivity and employee well-being (corporate level driver) and (iii) reputation and brand strategy (corporate level driver). Thus, it has been said that tenants have exhibited their willingness to pay for individual green features [12].…”
Section: Demands For Green Office Buildingmentioning
confidence: 99%
“…However, it has been shown that location can be a major influence on office occupation [2,3]. In another study, the other factors that pose an influence include real estate location, availability of sustainable buildings, and accessibility which remain to be of paramount importance [4].…”
Section: Introductionmentioning
confidence: 97%